2016
DOI: 10.1016/j.isprsjprs.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Information from imagery: ISPRS scientific vision and research agenda

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International licence Newcastle University ePrints-eprint.ncl.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 202 publications
(174 reference statements)
0
60
0
3
Order By: Relevance
“…This is due to the fact that segmentation is sensitive to many factors, like image sensor resolution, scene complexity or number of bands [6]. Object-based classification of VHR images represents a viable mobility, health, as well as safety and security and for this we need to deliver high-quality spatial information (i.e., timely, complete, reliable, geometrically and thematically accurate) [40]. Speed and accuracy are important factors when dealing with big remote sensing data or time conditioned events (e.g., earthquakes, tsunamis, landslides, refugees, tornados, oil spills etc.)…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that segmentation is sensitive to many factors, like image sensor resolution, scene complexity or number of bands [6]. Object-based classification of VHR images represents a viable mobility, health, as well as safety and security and for this we need to deliver high-quality spatial information (i.e., timely, complete, reliable, geometrically and thematically accurate) [40]. Speed and accuracy are important factors when dealing with big remote sensing data or time conditioned events (e.g., earthquakes, tsunamis, landslides, refugees, tornados, oil spills etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The ISPRS scientific research agenda reported in Chen et al (2015) identified an ongoing need for benchmarking in photogrammetry (Commission II) and open geospatial science in spatial information science (Commission IV). Recent efforts toward this goal include work by Rottensteiner et al (2014), Nex et al (2015), Campos-Taberner et al (2016), Koch et al (2016), and Wang et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [17] observe that more attention is required to calibration for precise geometric measurement tasks in image metrology and for unconventional imaging devices. Efforts have previously been made in the calibration of various digital-zoom lens devices, such as computer controllable lens systems [18,19], single-lens reflex cameras [16,20], still video cameras [21,22], pan-tilt-zoom (PTZ) systems [23,24], and industrial cameras [25].…”
Section: Related Workmentioning
confidence: 99%